Knowledge and attitudes of HIV pre-exposure prophylaxis among nurses in South Africa - Veronique C. Bailey; Atholl V. Kleinhans; Mathilda M. Mokgatle (AOSIS, 2023)
Background: Human immunodeficiency virus (HIV) pre-exposure prophylaxis (PrEP) has shown efficacy and effectiveness in populations who practise high-risk sexual activity. Nurses' knowledge and positive attitudes enhance PrEP implementation. Aim: This study aimed to investigate the knowledge of and attitudes towards PrEP among nurses in primary health care facilities. Setting: The study was conducted in 10 health facilities that offer comprehensive services in Tshwane, South Africa. Methods: A cross-sectional survey assessed the knowledge of and attitudes towards PrEP among 114 nurses. Univariate, bivariate and logistic regressions were performed to estimate odds ratios and to determine whether age, sex and education had an association with the knowledge and attitudes. Results: Majority of the study sample consisted of female nurses (92.1%), and most respondents (68%) had moderate PrEP knowledge. Logistic regression showed that age and education were not associated with high level of knowledge. Pre-exposure prophylaxis was viewed negatively by 84.5% of the respondents. The odds of positive attitudes towards PrEP were 1.92 times higher among males than females (95% CI 0.54-6.83) and 1.24 times higher among nurses who had bachelor's degree than diploma holders (95% CI 0.51-3.01). Conclusion: This study found that there is a need to strengthen the dissemination of information about PrEP, and nurses in South Africa require training to improve their knowledge of and attitudes towards PrEP. Contribution: The findings of the study add to the current knowledge base regarding PrEP access in the public healthcare system and it highlights gaps in the training of healthcare providers.